Effects of different rearing systems on carcase traits, physicochemical properties, basic chemical composition, fatty acid profiles and amino acid profiles of Gangba lamb - He Ding; Deqingzhuoga; Gesangjiacuo; Jize Zhang; Xiaoqing Zhang; Tana (Italian Journal of Animal Science, 2024)
This study aimed to explore the influence of feeding regimens on carcase traits and meat quality of Gangba lambs. Thirty healthy Gangba ram lambs at nine months of age and an average body weight of 14.08 ± 0.79 kg were randomly distributed into three treatment groups (10 replicates per group). The groups are as follows: a grazing (G) group without any supplementation and housing; a semi-grazing (SG) group provided with 200–300 g of concentrates and free access to oat hay off-pasture; and a stall-feeding (SF) group with 400–500 g of concentrates and free access to oat hay. The experiment lasted 85 d, comprising a 10-d adaptation period and a 75-d experimental period. Results showed that significant differences in carcase weight existed among groups, respectively, with the SF group having the highest weights and the G group having the lowest weights (p < 0.05). The pH45min and pH24h in the G group were significantly higher than that in the SG group (p < 0.05). Muscles from the G and SG groups had higher erucic acid (22:1n-9), α-linolenic acid (C18:3n3), and conjugated linoleic acids (CLA-c9t11 and CLA-t10c12) than the SF group (p < 0.05). The G group had a lower concentration of proline (Pro) than the SF group (p < 0.05). In conclusion, the feeding systems had no effects on chemical composition and little influence on amino acid composition. The traditional grazing rearing and SG systems improved lamb meat quality by increasing the presence of beneficial fatty acids. In contrast, the SF regimen improved the carcase weight of Gangba lambs without increasing their meat quality compared to the grazing rearing and SG systems. The directions of future efforts for breeders are to improve carcase traits (like carcase weight) of lambs in both natural grazing and SG systems, as well as the meat quality of lambs raised in feedlots.